The Socio-Religious Life of Mary in the Gospel of the Infancy of Jesus (Lk 1-2) - Mikołajczak, Mieczysław (Studia Warmińskie, 2011)
Recent discoveries in the realm of cultural anthropology and social psychology have had repercussions in our interpretation of the New Testament texts and particularly of the Gospel of the Infancy of Jesus (Lk 1-2). The author of this article has attempted to prove that scientific approach and scholarly models should be applied to these texts only in the context of broad theory of their origin and interpretation of the literary meaning. The author has narrowed down the scope of his interest to the presentation of the socio-religious status of Mary in Luke’s account (Lk 1-2). The research has shown how important it was for St. Luke. The final conclusion of the study is very significant and optimistic – presentation of Mary in Lk 1-2 signals the nature of salvation and the standards in the fellowship of God’s people which will be further developed in the next part of the double work of St. Luke (Lk – Acts).